A small molecule for a big transformation: topical application of a 20-nucleotide-long antisense fragment of the DIAP-2 gene inhibits the development of Drosophila melanogaster female imagos - Nyadar, Palmah M.; Oberemok, Volodymyr V.; Zubarev, Ilya V. (Archives of Biological Sciences, 2018)
Several genes have been identified to play important roles associated with sex selection in Drosophila melanogaster. An essential part is attributed to the sex-lethal gene that depends on the expression of the X:A (number of chromosomes to autosomes) ratio signal controlling both sex selection and dosage compensation processes in D. melanogaster. Interestingly, for sex selection in D. melanogaster there are no documented data addressing the role of the inhibitor of apoptosis (IAP) genes and their signaling influence on this biological process. In this study, we found that topical application of a 20-nucleotide-long antisense DNA fragment (oligoDIAP-2) from the death-associated inhibitor of apoptosis (DIAP)-2 gene interferes with D. melanogaster development and significantly decreases the number of female imagos and their biomass. We show that the applied antisense oligoDIAP-2 fragment downregulates the target DIAP-2 gene whose normal concentration is necessary for the development of female D. melanogaster. These data correspond to the results on downregulation of the target host IAP-Z gene of Lymantria dispar L. female imagos after topical treatment with an 18-nucleotide-long antisense DNA fragment from the Lymantria dispar multicapsid nuclear polyhedrosis virus IAP-3 gene at the larval stage. The observed novel phenomenon linking the downregulation of insect IAP genes and the low rate of female imago development could have practical application, especially in insect pest control and molecular pathology. https://doi.org/10.2298/ABS170302023N Received: March 2, 2017; Revised: April 29, 2017; Accepted: May 17, 2017; Published online: July 19, 2017 How to cite this article: Nyadar PM, Oberemok VV, Zubarev IV. A small molecule for a big transformation: Topical application of a 20-nucleotide-long antisense fragment of the DIAP-2 gene inhibits the development of Drosophila melanogaster female imagos. Arch Biol Sci. 2018;70(1):33-9.